Characterization of Acoustic Infrasound Signals at Volcán de Fuego, Guatemala: A Baseline for Volcano Monitoring - Diaz-Moreno, A.; Roca, A.; Lamur, A.; Munkli, B. H.; Ilanko, T.; Pering, T. D.; Pineda, A.; De Angelis, S. (Frontiers in Earth Science, 2020)
Monitoring volcanic unrest and understanding seismic and acoustic signals associated with eruptive activity is key to mitigate its impacts on population and infrastructure. On June 3, 2018, Volcán de Fuego, Guatemala, produced a violent eruption with very little warning. The paroxysmal phase of this event generated pyroclastic density currents (PDC) that impacted nearby settlements resulting in 169 fatalities, 256 missing, and nearly 13,000 permanently displaced from their homes. Since then, Volcán de Fuego has been instrumented with an extensive network of seismic and infrasound sensors. Infrasound is a new monitoring tool in Guatemala. A key step toward its effective use in volcano monitoring at Volcán de Fuego is establishing a baseline for the interpretation of the recorded signals. Here, we present the first comprehensive characterization of acoustic signals at Volcán de Fuego for the whole range of surface activity observed at the volcano. We use data collected during temporary deployments in 2018 and from the permanent infrasound network. Infrasound at Fuego is dominated by the occurrence of short-duration acoustic transients linked to both ash-rich and gas-rich explosions, at times associated with the generation of shock waves. The rich acoustic record at Fuego includes broadband and harmonic tremor, and episodes of chugging. We explore the occurrence of these signals in relation to visual observations of surface activity, and we investigate their source mechanisms within the shallow conduit system. This study provides a reference for the interpretation of acoustic signals at Volcán de Fuego and a baseline for real-time monitoring of its eruptive activity using infrasound data. Our results suggest that changes in the style of activity and morphology of the summit crater are reflected in the acoustic signature of eruption; as such our study provides a reference for the interpretation of acoustic signals at Volcán de Fuego and a baseline for real-time monitoring of its eruptive activity using infrasound.